Dengue epidemic in China before 1978 - Xiang Guo; Haiyang Chen; Ruifeng Lin; Xiaohua Liu; Meng Li; Liu Ge; Wenting Deng; Rangke Wu; Xiaohong Zhou (Infectious Diseases of Poverty, 2024)
Abstract Dengue, an acute febrile disease transmitted by Aedes mosquitoes, is caused by the dengue virus (DENV), presenting a formidable challenge to global public health. By examining clues from ancient Chinese books and conducting a comprehensive review, this study elucidates the characteristics of potential dengue epidemics in China prior to 1978. This evidence indicates that China may not have experience dengue epidemics before 1840. During 1840–1949, however, it experienced a noticeable dengue occurrence and prevalence in the 1870s, 1920s, and 1940s. Then from 1949 to 1978, only sporadic reports were accounted. The disparity in the frequency of dengue occurrences across three time periods suggests that the persistent characteristic of dengue epidemics in China primarily arises from imported cases resulting from international exchanges, subsequently leading to local outbreaks influenced by global epidemic trend. This research offers a novel perspective on retrospectively examining the historical trajectory of dengue epidemics and provides valuable insights into exploration of DENV epidemic patterns. Graphical Abstract